In-situ Synthesis rGO/NiO Nanorod Nanocomposites Via One-Step Hydrothermal Method and Investigating Physical Properties of Nanocomposites - Nguyen, Duc Tai; Luu, Thi Lan Anh; Nguyen, Huu Lam; Nguyen, Cong Tu (JST: Engineering And Technology For Sustainable Development, 2021)
In-situ nanocomposites of reduced graphene oxide (rGO) and niken oxide (NiO) nanowire were prepared by direct introducing homemade graphene oxide (GO) into precursor solution of NiO with different weight contents of GO (0.0, 0.5, and 1.0 wt.%) before carrying out the one-step hydrothermal process. Homemade GO was synthesized from graphene nanoflakes via Hummer method. Crystal structure and crystallinity of nanocomposites were analyzed using X-ray diffraction method. Scanning electron microscopy was used to study the morphology of nanocomposites. The absorbability of nanocomposites was evaluated through the absorption experiment with two organic dyes: methyl orange and congo red. The results show that compositing with GO does not affect the crystal structure of NiO but it causes the break of NiO nanorod into shorter nanorods, the increase of microstrain in NiO nanorods, and the increase of the absorption efficiency of nanocomposite with both methyl orange and congo red. The results are contribution to the study on hybrid/nanocomposite materials of carbon-based materials and metal oxide semiconductor nanostructures.